Copper‐Catalyzed Hydroamination of N‐Allenylazoles: Access to Amino‐Substituted N‐Vinylazoles. Issue 24 (16th October 2017) - Perego, Luca Alessandro; Blieck, Rémi; Michel, Julie; Ciofini, Ilaria; Grimaud, Laurence; Taillefer, Marc; Monnier, Florian
Abstract: Building on mechanistic studies, the innate capability of azoles to act as a directing group has been exploited to design an efficient and simple procedure for the hydroamination of N ‐allenylazoles with secondary amines. The reaction proceeds under mild conditions by copper(I) catalysis yielding the corresponding original linear E allylic amines with total regio‐ and stereoselectivity. Density Functional Theory (DFT) calculations offer a mechanistic explanation of the significantly higher reactivity of N ‐allenyl‐(1, 2)‐azoles compared to their 1, 3‐analogues as a result of the reaction‐enhancing coordination of the pyridine‐like nitrogen to the copper center. Abstract :